The Rhetoric of Retrenchment Themes and Values as Dimensions in an Interpretive Approach to Organizational Conflict - Yoder, Sharon Logsdon; Brenner, Donald J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
What characterizes the public communication behavior of members of an organization during the manifest stage of organizational conflict? To examine this issue, a study content-analyzed themes and values expressed in 212 news articles, editorials, and letters to the editor published by two community newspapers during a major public university's retrenchment debate. Theme statements were coded in five categories: financial, humanitarian, state and society, academic, and political. Value statements were coded in 20 categories, and further classified into four groupings: traditional academic values, interaction values, operational values, and environmental values. The debate was characterized by political theme statements, while themes of substance and those related to the particular organizational enterprise were submerged or decreased over the three-month period of debate. Values expressed in organizational members' statements reflected a similar pattern: organization-specific values were less frequently used and isolated in a linkage application of results. Environmental, interaction, and operational type values formed the character of the debate and provide potential application to communication in conflict situations in other organizations. Further, the values expressed by faculty, staff and students in the conflict (ranked by frequency of appearance in press coverage) had a near-zero correlation with identical values as ranked several years earlier in a survey inventory of the same population at the same university. (Five figures and eight tables of data are included, and 17 references are attached.) (SR)
ERIC Note: Paper presented at the Annual Meeting of the International Communication Association (36th, Chicago, IL, May 22-26, 1986). Study partially funded by Graduate Studies Center, School of Journalism, University of Missouri-Columbia.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Higher Education; Organizational Climate; Organizational Communication; Organizational Theories; Retrenchment; Communication Behavior -- Conflict Management; Communication Patterns -- Communication Strategies -- Organizational Culture; Speeches/Meeting Papers; Reports, Research